Yuzu the Pet Vet - Book 4 4 - Ito, Mingo; Goniwich, Julie; Nihon Koromubia Kabushiki Kaisha (2010- ) (New York : Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2020)
Continues Yuzus adventures assisting in an animal hospital, including encountering a young author who finds inspiration from her beloved bird, and helping her friend adjust to life with a young dog that is losing his sight.
"First published in Japan in 2018 by Kodansha Ltd., Tokyo" --Copyright page.
"In collaboration with Nippon Columbia Co., Ltd." --Cover.
Translated from the Japanese.
Keywords: Preteen girls -- Japan; Fiction; Veterinary hospitals -- Fiction; Veterinarians -- Fiction; Human-animal relationships -- Fiction; Pets -- Fiction; Birds as pets -- Fiction; Veterinary hospitals -- Comic books, strips, etc; Veterinarians -- Comic books, strips, etc; Human-animal relationships -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Fantasy comics; Graphic novels; Juvenile fiction